Adaptive Governance in Fire-Prone Landscapes. Issue 4 (3rd April 2022) - Platt, Emily; Charnley, Susan; Bailey, John D.; Cramer, Lori A.
Abstract: Wildfire is an influential driver of social and ecological change that calls for adaptive governance on federal lands. We identify supporting and limiting elements of adaptive governance in the context of wildfire management on the Deschutes National Forest (DNF). We use key findings to propose actions and leverage points to increase the US Forest Service's ability to engage in adaptive governance. Our research suggests that key supporting elements of adaptive governance within the Forest Service are generally found at the local scale. These supportive elements can be tapped to shed national-scale rigidity traps that lock the Forest Service into actions that have had problematic outcomes. The governance framework we used could be helpful in other research that aims to explore supporting and limiting elements of adaptive governance and identify high leverage points for change.